Editorial - Katherine Bullock (International Institute of Islamic Thought, 2007)
In July 2007, the Association of Muslim Social Scientists (AMSS) launched its new website: www.amss.net. This event signals a reinvigorated AMSS that seeks to update itself and enhance its professional image. The launch comes after several years of hard work, conducted mostly behind the scenes, on behalf of the AMSS Executive Board. Under the guidance of Dr. Rafik Beekun (president, AMSS), a recognized expert in strategic planning, AMSS has undergone a complete overhaul, from a SWOT (strengths, weaknesses, opportunities, threats) analysis to revising its by-laws and engaging in strategic planning, to implementation. In order to recognize the separate but related nature of Canada to the United States (it is not simply the 51st state!), as well as the prominent role being played by Canadian social scientists in AMSS, the board has suggested a new name: The Association of Muslim Social Scientists of North America. This is, of course, contingent upon the membership’s pending approval of the new by-laws. In addition, this name change helps identify us in relation to our sister organizations: AMSS-UK and AMSS-France. Each association is an independent entity sharing a common name, vision, and goals. The first AMSS international conference was held in Istanbul in 2006. One theme of AMSS’ new mission statement is that the organization will serve as an enabling environment for critical dialogue and debate between Muslim and non-Muslim scholars about issues of importance to the ummah and global society at large. The ability to dialogue is currently not one of the Muslim community’s strengths. Dialogue is about talking, about sitting down with people from different backgrounds in order to understand their perspective on often controversial issues. The point is not to convince them that your position is the “truth” or vice versa, but to hear them as fellow human beings and have them hear you. As the National Coalition for Dialogue and Deliberation points out, “dialogue is not about winning an argument or coming to an agreement, but about understanding and learning. Dialogue dispels stereotypes, builds trust and enables people to be open to perspectives that are very different from their own” (http://- thataway.org/index.php/?page_id=713) ...